Efektivitas Layanan Bimbingan Kelompok dengan Teknik Shame Attacking untuk Meningkatkan Self Disclosure SMK N 1 Tanjung Tiram - M. Jawahir Husaini Siagian; Nurussakinah Daulay (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
The purpose of this study was to determine the effectiveness of group guidance services using the Shame Attacking technique in improving students’ self-disclosure. This study employed a quantitative approach with a quasi-experimental research design, specifically a pretest–posttest control group design. The sample consisted of 16 students who were selected through purposive sampling based on low self-disclosure criteria and were then divided into two groups: 8 students in the experimental group and 8 students in the control group. Data were collected using a self-disclosure scale. The instrument applied in this study was an adapted version of the self-disclosure scale used in Tambubolon’s research, which was based on the same theoretical framework as the present study. Data analysis was conducted using the non-parametric Wilcoxon Signed Rank Test with the assistance of SPSS version 27. The hypothesis testing results showed an Asymp. Sig. (2-tailed) value of 0.012, which was lower than the alpha level of 0.05 (0.012 < 0.05). Based on these results, it was concluded that group guidance services using the Shame Attacking technique were effective in improving students’ self-disclosure.